(untitled) (TAJ: Journal of Teachers Association, 2021)
Background: Infection and Diabetes often coexist, making each other the worse for it. Patients with diabetes have a greater frequency and severity of many common infections such as urinary, pulmonary, soft tissue infections. This study aims to describe the bacterial agents and determine the antimicrobial susceptibility of diabetic foot infections (DFI) and pneumonia in the Rajshahi region. Materials and Methods: A descriptive study was performed over a period of one year in a tertiary care hospital that involved 120 patients. The aerobic bacterial agents were isolated, their antimicrobial susceptibility patterns were determined from wound swab and sputum samples. Results: A total of 106 microorganisms were isolated among 95 culture-positive cases. The microorganism isolated were 50.94% (n = 54) GN (Gram-negative) and 49.06% (n = 52) GP (Gram-positive). GN microorganisms include Pseudomonas spp. (25.47%), E. coli (14.15%), Klebsiella spp. (9.43%), and Proteus spp. (1.89%). S. aureus (38.68%) were predominant among GP, followed by S. pyogens (3.77%) and Enterococcus spp. (1.89%). About 4.72% were Coagulase Negative Staphylococcus (CoNS). S. aureus showed 95.12% sensitivity to Vancomycin and 90.24% to Imipenem. On the other hand, Pseudomonas spp. showed highest 85.19% sensitivity to Meropenem. Conclusion: Gram-negative (GN) microorganisms were predominantly isolated from DFIs and pneumonia, but S. aureus was the most frequently isolated organism. They showed a wide range of susceptibility towards different antimicrobials. TAJ 2021; 34: No-1: 09-15